2019
DOI: 10.1002/hpm.2791
|View full text |Cite
|
Sign up to set email alerts
|

What is the health cost of haze pollution? Evidence from China

Abstract: Summary Introduction Haze pollution has become a serious threat to the health of residents and has brought about considerable economic costs. The objectives of this study are to examine the relationship between haze pollution and residents' health and to estimate the health cost of haze pollution. Methods Using macro data on 74 major Chinese cities, this study employs a static panel data model and a dynamic panel generalized method of moments model to investigate the impact of haze pollution on the mortality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…33 Through this analysis, we developed a coefficient quantifying the relationship between particulate matter (PM) 2•5 concentration and IQ loss in children younger than 10 years. Details are presented in the appendix (pp [13][14][15][16].…”
Section: Estimation Of Intelligence Quotient (Iq) Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…33 Through this analysis, we developed a coefficient quantifying the relationship between particulate matter (PM) 2•5 concentration and IQ loss in children younger than 10 years. Details are presented in the appendix (pp [13][14][15][16].…”
Section: Estimation Of Intelligence Quotient (Iq) Lossmentioning
confidence: 99%
“…31 From these data, we calculated that the slope of the relationship between PM 2•5 concentrations and PIQ loss in this range is -0•61 PIQ points per 1 μg/m³ increase in PM 2•5 . Details are presented in the appendix (pp [13][14][15][16][17].…”
Section: Rwandamentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] Air pollution leads to increased healthcare expenditure, social costs, and economic pressures. 21,22 A comprehensive study of the indicators of medical expenses caused by air pollution benefits the development of evidence-based and health-related environmental policymaking, 23 especially for ischemic stroke, a disease with high incidence and significant resource consumption. Several studies have shown a positive association between air pollution exposure and increased medical expenses.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of researchers have found that air pollution has an impact on the mortality and morbidity of ischemia 14–16 . Air pollution leads to increased healthcare expenditure, social costs, and economic pressures 21,22 . A comprehensive study of the indicators of medical expenses caused by air pollution benefits the development of evidence‐based and health‐related environmental policymaking, 23 especially for ischemic stroke, a disease with high incidence and significant resource consumption.…”
Section: Introductionmentioning
confidence: 99%